PENJUALAN , PENDAPATAN DAN PAJAK PERTAMBAHAN NILAIPERUSAHAAN ANGKUTAN UDARA NIAGA BERJADWAL - Sudarno, Sudarno (Jurnal Ilmiah Kedirgantaraan, 2018)
Revenue comprises  turnover from transportation of passenger and cargo and this provision of other services, e.g engineering and maintenance,leasing and package holidaysThe treatment of passenger and cargo in external financial statements would generally appear to be consistent in industry,as a result this guideline cover both aspects of revenue without differentiating unless reference is made.The basic principal that revenue should be recognised when transportation or carriage provided is well established.This concept is the same whether revenue passenger and cargo.This treatment reflect the application of the accruals concept(accruals basis).The airlines in effect  act as collectors on  value added tax from sold of passenger ticket or air way bill and other service  amounting to 10 %(ten percent) from  face value.Treatment of accounting policy as follows;1.Income arisingfrom sales made where the sale coupon has been processed, but  the flight is yet to  take place and recorded in the accounting period as unearned  revenue  ,included in current liabilities2.If flight  coupon has been flight to destination but have been not  recorded in  the account  of ticket sold called unrecorded  included in current asset,for value added tax purposes  unrecorded can be changed to account receivables.3.Scheduled and charterrevenue from passengers and recorded in the accounting periode as income included in statement  of income.4.All forms of cargo revenue derived from air freight and recorded in the accounting period as income included in statement of income